Regulating Coastal Setbacks Through Spatial Planning Law Enforcement - I Gede Andi Iswarayana; I Made Suwitra; I Wayan Rideng (Inovasi Pratama Internasional. Ltd, 2026)
This study examines the enforcement of spatial planning law in regulating coastal setback utilization in Nusa Penida, Klungkung Regency, Bali, where rapid tourism development has intensified pressure on protected coastal zones. The research aims to assess the effectiveness of legal enforcement mechanisms in controlling coastal setbacks and to identify institutional and regulatory factors that hinder compliance. An empirical legal research design is adopted, integrating statutory, conceptual, and sociological approaches. Primary data were gathered through semi-structured interviews with local government officials and relevant stakeholders, while secondary data were obtained from legislation, regional spatial planning documents, and official records. Qualitative analysis was conducted by relating normative spatial planning provisions to observed enforcement practices in the study area. The findings indicate that coastal setback regulation has not been effectively implemented, largely due to the absence of detailed spatial planning instruments, limited supervisory capacity, and reliance on administrative discretion rather than clear technical standards. These conditions weaken legal certainty and constrain the consistent application of zoning rules and sanctions. The study concludes that the formulation of detailed spatial plans and the strengthening of enforcement mechanisms are critical to improving coastal setback governance and supporting sustainable coastal management in island tourism regions.